PENGARUH PENGGUNAAN MEDIA JOBSHEET DAN KREATIVITAS TERHADAP TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN SENI RUPA DI SMPN 4 BUKITTINGGI - Tri Dinda Sahira, Drs. Wisdiarman, M.Pd. (Serupa The Journal of Art Education, 2019)
This research is raining to see the comparison of the students’ visual art learning outcomes who have high creativity and low creativity taught with Jobsheet and conventional media. This research uses quasi-experimental methods with 2 x 2 forms. For the implementation, intial knowledge, final knoeledge, and creativity tests are conducted on both classes. The results of this study were students who were treated, learning outcomes were better than students who were not treated. For this reason, the use of Jobsheet media is very good to be applied to students in art learning, especially pratical learning.Keywords: Jobsheet media, creativity, learning outcomes